STRATEGI KOMUNIKASI SMPN 1 JETIS DALAM MELESTARIKAN SENI BUDAYA REOG PONOROGO - Rifki Aulia; Rila Setyaningsih (Mediakita, 2019)
Maintaining the preservation of local culture is a necessity in the era of the development of the industrial revolution 4.0, especially among the younger generation. Jetis 1 Junior High School is the only school in Ponorogo that holds a Reog Festival between classes each year. This is one indicator that the school is still concerned with the preservation of local culture in the midst of the onslaught of technology and the development of a disruptive era. The purpose of this study was to analyze the communication strategies of Jetis 1 Jetis in preserving Reog Ponorogo cultural arts. The method used in this study consisted of interviews, observations and documentation. Data analysis is performed through data collection, data reduction, data presentation, and drawing conclusions. Data validity uses triangulation of sources and methods. The results showed that Jetis 1 Jetis had carried out all stages of the communication strategy of getting to know the audience, composing messages, setting methods, and choosing media, but the overall implementation was not optimal. This research is expected to contribute to improving communication strategies in preserving Reog Ponorogo cultural arts especially through educational institutions.